Asian Australian media representation of First Nations sovereignty and constitutional change - Huck Ying Ch'ng; Kashifa Aslam; Huong Nguyen; Bradley Smith (2022)
This study explores levels of interest in and framing of Australian First Nations constitutional reform in minority ethnic media. A keyword search of mainstream English media in Australia and of media targeted at Chinese, Pakistani, Vietnamese and Indonesian Australian communities shows a relatively low level of interest in the publication of and government response to the Uluru Statement in the latter outlets compared to the English media. Framing analysis over an extended timeframe finds some interest in and broad support for Australian First Nations’ calls for constitutional reform in the Asian Australian media, as well as variation and suggestive correlations between framing and audience such as linking First Nations history to experiences of racism and exclusion of Chinese Australians. The study has implications both for any referendum for a First Nations Voice to Parliament and for scholarship on the role of minority ethnic media in the contemporary Australian public sphere.